Expression of the myosin light chains 1, 2 and 3 in the muscle of blackspot seabream (Pagellus bogaraveo, Brunnich), during development - Silva, P (2010)
Previous studies on the histochemistry and immunoreactivity of fibres in lateral muscle of blackspot seabream indicated that there is a developmental transition in the composition of myofibnllar proteins, which presumably reflects changes in contractile function as the fish grows We hypothesize that the phenomenon underscores age and spatial differences in the expression of myosin light chains (MLC), not studied yet in this species In this study, we examined selected stages in the post-hatching development of the muscle of blackspot seabream hatching (0 days), mouth opening (5 days), weaning (40 days) and juveniles (70 days) The spatial expression of embryonic MLC 1 (MLC1), 2 (MLC2) and 3 (MLC3) was studied by in situ hybndization Overall, MLC expression patterns were overlapping and restricted to the fast muscle At hatching and mouth opening, all MLC types were highly expressed throughout the musculature in fast muscle The expression levels in fast muscle remained high until weaning when germinal zones appeared on the dorsal and ventral areas The germinal zones were characterized by small-diameter fast fibres with high levels of MLC expression This pattern persisted up to day 70, when the germinal zones disappeared and expression of MLCs was observed only in the smaller cells of the fast muscle mosaic These results support our hypothesis and, together with previous imuno-and histochemistry results, allow a better understanding of the mechanism of muscle differentiation and growth in fish beyond larval stages, and form- the basis for further comparative and experimental studies with this economically relevant species